Study of Drug Prescription Pattern of Obese and Non-Obese Patients with Type-II Diabetes with or without Hypertension - Bajracharya, Mijala; Nakarmi, S (Journal of Manmohan Memorial Institute of Health Sciences, 2020)
Correction: The page numbers were changed from 98-100 to 81-93 on 31/08/2020.Background: Obesity is regarded as worldwide health problems which may put a person at a higher risk of serious health conditions leading to morbidity and mortality. Obesity is a risk factor for many diseases of which hypertension and type-2 diabetes mellitus are the most important. Hypertension, diabetes mellitus and obesity together form 24% of the global risk for mortality. Cardiovascular diseases related to these life-style disorders has major effect on life expectancy and impaired quality of life.Objectives: The study was done to evaluate the drug prescribing pattern of type - 2 diabetes and hypertension in both obese and non-obese patients. Along with it, this study also attempt to find the contributing factors associated with it and different types of drugs selected in those conditions respectively. Method: A descriptive cross-sectional study was conducted in 2074 at Manmohan memorial teaching hospital. A total of 101 out-patient were interviewed, measurements were done to calculate BMI and waist to hip ratio and their prescriptions were reviewed. For Treatment Guideline of HTN, JNC 8[20] was followed and Updated Treatment Guidelines for Type 2 Diabetes by the American Diabetes Association (ADA) [21] was followed in case of diabetes. Result: Among 101 patients studied, 58 were males and 43 were females. Regarding physical activity, only 26.7% of total patients were involved in morning walk and 3% in yoga, remaining 71% of study patients did not involve in any kind of physical exercise. Regarding food habits, 22.8% were smokers, 49.5% were alcoholics and 96% were non-vegetarians. Waist to hip ratio was also observed higher in both males (35.6%) and females (39.6%). Among the101 total participants, the age group of 41-55 years were found to be more obese than other age group (34 in numbers) followed by age group 56-70 which were 16 in numbers. Male patients were more obese (41) than female patients (31). Highest number (31) of the obese patients were diagnosed with type 2 diabetes mellitus, followed by second highest number (26) of patients diagnosed with hypertension and 15 patients with both the conditions. The commonly prescribed oral hypoglycemic drugs were metformin (35.60%) followed by glimepiride (24.80%). Among anti-hypertensive drugs, amlodipine (22.80%) was most common in prescriptions followed by losartan (18.80%) and Telmisartan (17.80%). Conclusion: The results of the present study show that higher number of male patients (41) were obese than female patients (31). About 30% of patients were found obese-diabetic, 26% were obese-hypertensive and 15% were with both obese diabetic and hypertensive condition. Among oral hypoglycemic drugs, metformin (35.60%) was mostly prescribed followed by glimepiride (24.80%). Among antihypertensives, amlodipine (22.8%) was mostly prescribed followed by losartan (18.80%). Atorvastatin (11.9%) was mostly prescribed oral hypolipidemic agent.